2011
DOI: 10.2146/ajhp100492
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic benefits of aromatase inhibitor therapy in early-stage breast cancer

Abstract: AI therapy has become a standard of care for the treatment of most postmenopausal women with early-stage breast cancer. Emerging data have demonstrated potential overall survival advantages for AIs subsequent to and directly related to distant recurrence. When the economic burden to society is considered, it appears that all AIs are similarly beneficial on the basis of disease recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Data from clinical studies have suggested a usefulness of aromatase inhibitors in preventing early stage distant metastases, and, therefore, it has been proposed that initial therapy involving adjuvant use of aromatase inhibitors can be beneficial against tumor recurrence [160, 161]. For many years, a five-year administration of tamoxifen has been the gold standard for endocrine therapy in ER-responsive breast cancer patients, and this notion is increasingly being challenged with the inclusion of aromatase inhibitors in the initial years of therapy [162].…”
Section: Therapeutic Options To Prevent Breast Cancer Recurrencementioning
confidence: 99%
“…Data from clinical studies have suggested a usefulness of aromatase inhibitors in preventing early stage distant metastases, and, therefore, it has been proposed that initial therapy involving adjuvant use of aromatase inhibitors can be beneficial against tumor recurrence [160, 161]. For many years, a five-year administration of tamoxifen has been the gold standard for endocrine therapy in ER-responsive breast cancer patients, and this notion is increasingly being challenged with the inclusion of aromatase inhibitors in the initial years of therapy [162].…”
Section: Therapeutic Options To Prevent Breast Cancer Recurrencementioning
confidence: 99%
“…Similarly, using data from the Henry Ford Health System, the mean monthly charges were highest for distant recurrence ($37,969), followed by locoregional ($10,934) and contralateral ($9,129) recurrence, when calculated for the year immediately after the recurrence 83. In the United Kingdom National Institute for Health Research analysis, other costs associated with AIs compared to tamoxifen were $8,032 (exemestane) versus $8,290, $7,491 (anastrozole) versus $7,770, and $6,781 (letrozole) versus $7,156 81. The percentage increase in cost is largest between letrozole and tamoxifen and is possibly because of a significantly reduced risk of recurrence at distant sites 82…”
Section: Patient Preference and Health-related Quality Of Life Measurmentioning
confidence: 99%
“…Endocrine therapy plays a key role in treatment and management of hormone receptor-positive breast cancers [11]. A number of recent reviews [12][13][14][15][16] have identified up to 20 different CEAs comparing endocrine therapeutic strategies, most of which included either tamoxifen or anastrazole for treatment of hormone receptor-positive adjuvant breast cancer (ABC). However, none of these reviews specifically addressed the impact of structural uncertainty for CEAs comparing endocrine breast cancer treatments.…”
Section: Introductionmentioning
confidence: 99%